Oberflächenfeinbearbeitung keramischer Werkstoffe mit XeCl-Excimerlaserstrahlung - Lutz, Norbert (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1994)
The aims of the work were fundamentals of surface modification and micro machining of ceramics with XeCl excimer laser radiation and the deduction of hints for industrial application. The surface modification of ceramics is a very promising field of application for excimer lasers. Depending on the energy density and the pulse number the surface can be roughened or smoothed using low pulse numbers. Thin layers of the material are removed above the ablation threshold. A projection scheme produces a demagnified image of the mask at the surface. Lateral dimensions of less than ten microns are obtained with this technique. The observation that the ablation rates increase with increasing temperature of the workpiece can be of technological interest as the processing times can be reduced. The investigation clearly indicates that excimer lasers have the potential for precise machining of ceramic